A study of the relationship between physical fitness, physical and psychological development and their impact on the level of special training among seven-year-old hockey players - Abramova T.F. ,; Nikitina T.M. ,; Balabokhina T.V. ,; Shachnev E.N. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the relationship between indicators of physical fitness, physical and psychological development and manifestations of special fitness in hockey players aged seven. Methods and structure of the study. 27 young hockey players took part in the experiment: the average age was 7.1±0.22 years; the training experience was 2.3±0.22 years; the average weekly training volume was 11.6±2.5 hours. The following body sizes and proportions were studied; variable components of body weight; abilities: psychomotor, cognitive and motor (30 m sprint; 3x10 m shuttle run; 3x10 m alternating running (regular, side-by-side, back-to-back); long jump from a standing position; grip strength) in conjunction with the results of standardized tests. tests evaluating special training in hockey, using Spearman correlation analysis. Results and conclusions. It has been established that the formation of special sports skills among hockey players in the second year of training at the sports and recreation stage of training at a medium-low level of correlation mainly depends on the degree of physical fitness, to a lesser extent on the development of psychomotor skills, morphofunctional and cognitive characteristics. In athletes aged seven, the level of special training is mainly determined by the ability to resist interference, the speed and strength characteristics of the legs, the state of autonomic regulation and the formation of a specific muscular balance of the body.